Marketing Politik: Urgensi dan Posisinya dalam Komunikasi Politik - Anugerah, Dadan (Jurnal Ilmu Dakwah, 2011)
The politics could said as branch way so multitude with all disciplines passed by it. It is like âoaseâ place that constitute meeting place of variety of science discipline, that in one day born political sociology, political psychology, political communication, and also political marketing. However, itâs born academically can be said young, political marketing able to attract attentions of social scientists and political practitioner. In earlier, the term of marketing used in business world for wining competition in business. But, to day, the political process also not miss from marketing with goal sell the idea, platform, and so on of a candidate and political party.